2014
DOI: 10.1111/all.12409
|View full text |Cite
|
Sign up to set email alerts
|

The KITD816V allele burden predicts survival in patients with mastocytosis and correlates with the WHO type of the disease

Abstract: KIT D816V is present in a majority of patients with systemic mastocytosis (SM). We determined the KIT D816V allele burden by quantitative real-time PCR in bone marrow and peripheral blood of 105 patients with mastocytosis. KIT D816V was detected in 92/105 patients (88%). Significant differences in the median allele burden were observed among disease subgroups; cutaneous mastocytosis (0.042%), indolent SM (0.285%), smoldering SM (5.991%), aggressive SM (9.346%) and SM with associated hematologic non-mast cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
66
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 15 publications
2
66
1
3
Order By: Relevance
“…61 In addition, our findings might also contribute to explain why ISM patients with MC-restricted KIT mutation in the BM have a normal life expectancy and very rarely progress to more aggressive disease. 7 Of note, here, we reported a higher rate of progression of ISM patients than that observed in previous (large) series of ISM patients 7,54,62 ; this is probably due to the preferential selection of cases with multilineage involvement of hematopoiesis by the KIT D816V mutation vs MCrestricted KIT D816V mutation because the latter cases typically showed very low rates of disease progression 7 and/or a longer follow-up in this vs other previously reported series.…”
Section: Discussioncontrasting
confidence: 47%
“…61 In addition, our findings might also contribute to explain why ISM patients with MC-restricted KIT mutation in the BM have a normal life expectancy and very rarely progress to more aggressive disease. 7 Of note, here, we reported a higher rate of progression of ISM patients than that observed in previous (large) series of ISM patients 7,54,62 ; this is probably due to the preferential selection of cases with multilineage involvement of hematopoiesis by the KIT D816V mutation vs MCrestricted KIT D816V mutation because the latter cases typically showed very low rates of disease progression 7 and/or a longer follow-up in this vs other previously reported series.…”
Section: Discussioncontrasting
confidence: 47%
“…At the same time, our results suggest that a minimum number of mutated cells circulating in peripheral blood may be required to identify bone marrow multilineage involvement in peripheral blood, as suggested by the better results found once the qualitative results of the allele-specific oligonucleotide-qPCR technique were replaced by a quantitative (allele burden) threshold. In line with this, Hoermann et al 14 recently showed that systemic mastocytosis with a higher bone marrow allele burden (42%) have a greater probability of showing disease progression. However, it should be noted that, despite the higher allele burden for the KIT mutation observed in our series in the peripheral blood of cases showing multilineage vs mast cellrestricted KIT mutation, still half of systemic mastocytosis patients who showed multilineage bone marrow involvement had KIT allele burden values in peripheral blood below the most specific cutoff identified (6% KIT-mutated peripheral blood cells).…”
Section: Discussionmentioning
confidence: 71%
“…10 In line with this hypothesis, new highly sensitive methods have been described, 13 which allowed detection of the KIT D816V mutation in peripheral blood leukocytes from most mastocytosis cases, including 66/69 (96%) indolent systemic mastocytosis and 3/4 cutaneous mastocytosis investigated. 9,14 Despite this, the potential relationship between the presence of the KIT D816V mutation in peripheral blood and multilineage involvement of bone marrow hematopoiesis has not been investigated so far. In this regard, particularly intriguing is the potential lack of association between the allele burden for the KIT mutation in peripheral blood, as assessed by the allele-specific oligonucleotide polymerase chain reaction (allelespecific oligonucleotide-qPCR), and the clinical and biological features of indolent systemic mastocytosis.…”
mentioning
confidence: 99%
“…3,4 Indeed, type and severity of symptoms are independent of KIT Asp816Val status. 1,5,6 Masitinib is an oral tyrosine kinase inhibitor that targets wild-type KIT (50% inhibitory concentration [IC 50 ] 200 nM) with greater potency in vitro than KIT Asp816Val (IC 50 5·0 μM), as well as targeting LYN and FYN at submicromolar concentrations. 7 Wildtype KIT, LYN, and FYN have crucial roles in the survival and function of mast cells, including mediator release.…”
Section: Introductionmentioning
confidence: 99%